2010
DOI: 10.1260/2041-4196.1.3.299
|View full text |Cite
|
Sign up to set email alerts
|

A New Methodology for the Assessment of the EoS Data of Concrete

Abstract: The experimental determination of the equation of state is a complex and expensive task. This paper presents a new methodology for the theoretical determination of the equation of state for concrete. Mesomechnical simulations are conducted and compared to three sets of experimental data. It was also investigated whether the methodology used for the meso-scale modeling is applicable to a homogenized description of concrete. Based on more than 400 numerical simulations, it is shown that the EoS parameters which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Owing to the lack of true tri-axial testing data, especially the data under cyclic loading, the current EOS models in general assume the linear unloading path following the initial bulk modulus and reloading path following the unloading path to the point where the unloading begins. Although these constitutive models have been proven by many researchers yielding good predictions of concrete structure response and damage to blast and impact loads (Chen et al, 2015;Li and Hao, 2014;Qian et al, 2021), some recent studies (Cui et al, 2017;Gebbeken and Hartmann, 2010) revealed that the unloading and reloading path of concrete material are not linear owing to the internal damage caused by deviatoric stress existing in concrete specimen even under hydrostatic loadings induced by the heterogeneity properties of the concrete material. Reviewing and discussion the EOS of concrete material is beyond the scope of this paper.…”
Section: Response Of Secondary Structures Under Internal Explosionsmentioning
confidence: 99%
“…Owing to the lack of true tri-axial testing data, especially the data under cyclic loading, the current EOS models in general assume the linear unloading path following the initial bulk modulus and reloading path following the unloading path to the point where the unloading begins. Although these constitutive models have been proven by many researchers yielding good predictions of concrete structure response and damage to blast and impact loads (Chen et al, 2015;Li and Hao, 2014;Qian et al, 2021), some recent studies (Cui et al, 2017;Gebbeken and Hartmann, 2010) revealed that the unloading and reloading path of concrete material are not linear owing to the internal damage caused by deviatoric stress existing in concrete specimen even under hydrostatic loadings induced by the heterogeneity properties of the concrete material. Reviewing and discussion the EOS of concrete material is beyond the scope of this paper.…”
Section: Response Of Secondary Structures Under Internal Explosionsmentioning
confidence: 99%
“…a) Hydrostatic pressure vs volumetric strain for different tests; b) Load path for different tests. [26,27,49,51,63]. Micro-plane models [64] and particle methods [42,43] are also some particular types of mesoscopic models used for concrete.…”
Section: Concrete Models Brief Reviewmentioning
confidence: 99%
“…(1) permits their projection onto the compressive meridian (θ = 60°) and the formulation of a descriptive function. In the model the compressive meridian of the fracture surface Y max is defined by a power function which has the form (2) where p* represents the hydrostatic pressure normalized by the uniaxial compressive strength. This scaling is necessary to determine the material parameters M and E from a broad basis of experimental data from various concrete mixtures with different strengths.…”
Section: S St Tr Re En Ng Gt Th H M Mo Od De El L 21 Formulatimentioning
confidence: 99%
“…The shifting parameter A trans in Eqn. (2) does not represent an independent material parameter. It can be calculated from the equation 3so that Eqn.…”
Section: S St Tr Re En Ng Gt Th H M Mo Od De El L 21 Formulatimentioning
confidence: 99%